FRI0598 A SYSTEMATIC REVIEW OF THE EFFECTIVENESS AND SAFETY OF PHARMACOLOGICAL TREATMENTS IN PATIENTS WITH SYSTEMIC IDIOPATHIC JUVENILE ARTHRITIS (SJIA). (June 2019) - Kuemmerle-Deschner, Jasmin; Thakur, Lalit; George, Aneesh; Hur, Peter
Abstract : Background: Treatment options for SJIA include canakinumab, tocilizumab (both approved by US FDA and EMA) and anakinra (approved by EMA), while anti-tumor necrosis factor inhibitors, steroids, disease-modifying anti-rheumatic drugs and non-steroidal anti-inflammatory drugs are also used. 1 A recent systematic review included only randomized controlled trials (RCTs) of biologics. We aimed to generate a more comprehensive evidence on the effectiveness and safety of treatments used in SJIA. Objectives: To assess evidence on the effectiveness and safety of therapeutic agents for SJIA from RCTs and real-world studies. Methods: A systematic literature review was conducted using Cochrane methodology 2 from 2000 to Jan 2018. Sources included Embase®, MEDLINE®, MEDLINE®-In Process and Cochrane library. Studies were searched for English language publications as full-text articles (2000 to Jan 2018) or conference abstracts (2015 to Jan 2018). Studies with ≤15 pts were excluded. Results: Of the 62 included studies, 8 were RCTs and 54 were real-world studies. The interventions included in the RCTs were anakinra (ANA), canakinumab (CAN), etanercept (ETN), methotrexate (MTX) and tocilizumab (TCZ) (1 RCT each and 1 withdrawal trial for TCZ), and 2 RCTs for rilonacept (RLN); all vs. placebo (PLB). In addition to the interventions mentioned in the RCTs, real-world studies also included other interventions such as abatacept, adalimumab (ADA), infliximab (INF), non-steroidal anti-inflammatory drugs and steroids. Juvenile idiopathic arthritis - American college of rheumatology (JIA ACR)-30 was the most common composite outcome reported across studies. In RCTs, the JIA ACR-30 (+ no fever) responses were significantly superior vs. PLB for CAN (81% vs. 10%), TCZ (85% vs. 24%), and ANA (92% vs. 50%) (p<0.05 for all), while other interventions (RLN and MTX) were less responsive. Additionally during the trial extension period, the inactive disease rates were 57%, 31% and 31% for TCZ, CAN and ANA respectively. In real-world studies, the JIA-ACR 30 response rates reported for ANA, ANA or CAN (patients were on either therapy), TCZ and ETN were 50%-55%, 57%-60%, 47%-100% and 47%-73% at short-term follow-up period (FUP, <12 months), while the corresponding response rates at long-term FUP (≥12 months) were 45%, 51%-63%, 58%-100% and 60%-100%. For ADA and ADA or ETN or INF (patients were on either therapy), while the JIA-ACR response rates at short term FUP were not reported, the response rates at long-term FUP were 100% and 78% respectively. Additionally, juvenile arthritis disease activity score (JADAS)-10 ≤ 1 scores were reported for ANA or CAN, CAN, ETN and TCZ as 52%, 48%-91%, 20% and 36% at short-term FUP. The mean changes in JADAS-71 scores at short-term FUP for ANA and TCZ were 10% and 11% respectively while the corresponding scores at long-term FUP were 13% and 14% (p<0.001). All interventions were generally well tolerated by SJIA patients; infections, injection site reactions and macrophage activation syndrome were reported for all biologics. Other complications included gastrointestinal disorders, pharyngitis, skin disorders, increase in liver enzymes etc. Conclusion: The current interventions especially ANA, CAN, ETN and TCZ were found to be effective and generally well tolerated in SJIA. However, the lack of head-to-head studies limits a rigorous comparison. References: [1] Ringold, et al. 2013. Arthritis Rheum;65:2499-512. [2] Higgins, et al. 2011. Cochrane Handbook for Systematic Reviews of Interventions Version5.1.0. Disclosure of Interests: Jasmin Kuemmerle-Deschner Grant/research support from: Jasmin Kuemmerle-Deschner is an employee of University of Tuebingen, Germany, and received consultants/speakers fees from Novartis and SOBI pharmaceuticals and grant support from SOBI and Novartis., Consultant for: Jasmin Kuemmerle-Deschner is an employee of University of Tuebingen, Germany, and received consultants/speakers fees from Novartis and SOBI pharmaceuticals and grant support from SOBI and Novartis., Speakers bureau: Jasmin Kuemmerle-Deschner is an employee of University of Tuebingen, Germany, and received consultants/speakers fees from Novartis and SOBI pharmaceuticals and grant support from SOBI and Novartis., Lalit Thakur Employee of: Lalit Thakur is an employee of Novartis Healthcare Pvt. Ltd., Hyderabad, India, Aneesh George Employee of: Aneesh George is an employee of Novartis Healthcare Pvt Ltd., Peter Hur Employee of: Peter Hur is an employee of Novartis Pharmaceuticals Corporation, East Hanover, New Jersey, USA